BARTULIS’ EXPRESSION IN THE OPERA (Mūzikas akadēmijas raksti, 2024)
Among the most prominent opera composers in Lithuania Vidmantas Bartulis stands out as an author of non-typical solutions who values an unrepeating fantasy of the moment. Alongside with his operas mention must made of the The Lamb of God (Dievo Avinėlis, 1981–1982) by Feliksas Bajoras which consolidated the idea of polylogue and related, in a manner different from that of Thrush – the Green Bird (Strazdas žalias paukštis, 1981) by Bronius Kutavičius, the contemporary language, ethno signs and deep authenticity as well as the archetypical expression of Lithuanian thought. Opera The Bear (Lokys, 2000) by Kutavičius in a postmodernistic view presents us with a myth of barbaric ancestors and synthesizes the major part of Kutavičius’ early works through the language of music. In terms of its drastic plot the opera is closer to Bartulis’ A Lesson (The Pamoka, 1993).